The Experimental Research of the Temperature in the Vicinity of Worm wheel Tooth Surface - 孙月海; 王树人; 程福安 (Jixie chuandong)
In the worm driving,a series of temperature values of typical points in the vicinity of a worm wheel tooth surface were gained by means of thermocouple under the conditions of different torques.The distribution feature and the fluctuation tendency of the temperature in the vicinity of the worm wheel tooth surface were investigated and analyzed.